2011
DOI: 10.1117/12.877754
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided tissue characterization using ultrasound-induced thermal effects: analytical formulation and in-vitro animal study

Abstract: Ultrasound radio-frequency (RF) time series analysis provides an effective tissue characterization method to differentiate between healthy and cancerous prostate tissues. In this paper, an analytical model is presented that partially describes the variations in tissue acoustic properties that accompany ultrasound RF time series acquisition procedures. These ultrasound-induced effects, which depend on tissue mechanical and thermophysical properties, are hypothesized to be among the major contributors to the tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…It should be noted that the characterization capabilities of RF time series have been successfully demonstrated elsewhere with different users, transducers and systems, and extensive parameter ranges, for differentiation between various ex vivo animal tissue types and identification of prostate cancer in ex vivo human prostate [33], [37], [46]. We plan to extend this study to assess the effect of various ultrasound transducers.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that the characterization capabilities of RF time series have been successfully demonstrated elsewhere with different users, transducers and systems, and extensive parameter ranges, for differentiation between various ex vivo animal tissue types and identification of prostate cancer in ex vivo human prostate [33], [37], [46]. We plan to extend this study to assess the effect of various ultrasound transducers.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, the area under the ROC curve for the RF time series features is close to 1 compared to 0.8 for spectral features. Previously, it was shown that temperature rise produced by acoustic propagation may be the major contributor to the ability of time series analysis for tissue typing [7]. In other words, the speed of acoustic waves in the tissue is dependent on the tissue temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of physiologic motion in ex-vivo experiments, the tissue typing characteristics of RF time series were potentially due to the minute temperature changes caused by continuous sonification. The hypothesis was investigated in Daoud et al (2011), Daoud et al (2013). In Imani et al (2013), the RF time series signals prior to, and at the end of the ablation process are analyzed for lesion detection.…”
Section: Rf-signal-based Approachesmentioning
confidence: 99%